Improvement of hydration products for self-compacting concrete by using magnetized water (Fracture and Structural Integrity, 2022)
Magnetized water (MW) is one of the most effective and economical ways to improve the properties of self-compacting concrete (SCC). Therefore, the aim of this study is to improve the fresh, mechanical, and microstructural properties of SCC using MW. For this purpose, a total of 12 mixes were produced with silica fume (SF) content (5% and 10% by weight of cement), and the mixing water passed through a permanent magnetic field (with a strength of 1.4 T) for 50, 100, and 150 cycles. Tests were performed for fresh properties (Slump flow, T50cm, V-funnel, and L-box), for mechanical properties (compressive, flexural, and tensile strength), and for microstructure properties (SEM, EDX, and TGA/DTG). The optimum result in compressive strength was achieved in the mix M8 using 5% silica fume and 150 cycles of MW. For fresh properties, the mix M4 using 150 cycles without SF had the workability enhanced by 11% compared to the control mix, and SEM and EDX tests indicated that SCC mixes prepared with MW had more C-S-H, less CH, and were denser. In addition, TGA/DTG analysis showed that the rate of hydration of mix M8 was reached by 61% at 28 days.
Keywords: Self-Compacting concrete; Sustainable concrete; Magnetic water; Rate of hydration